The Stylistic Dimension of Language in the Age of Adaline Movie - Resha Aldo Saputra; I Komang Sumaryana (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study explores the stylistic and functional dimensions of language in The Age of Adaline movie by analyzing the types of language style and function used in the script. Grounded in Martin Joos’ theory of language style and Roman Jakobson’s theory of language function, the research adopts a qualitative method with a discourse and sociolinguistic analysis approach. The study aims to identify how various styles and functions of language are utilized to shape character interactions and support the narrative. The findings reveal the presence of all five language styles proposed by Joos: casual style occurred most frequently (35 instances), followed by consultative (8), intimate (8), formal (5), and frozen (1). This distribution indicates a dominant use of casual language to reflect everyday, spontaneous conversation among characters. In terms of language function, the study identified four out of six functions: referential (21 instances), emotive (19), conative (10), and phatic (7). However, metalingual and poetic functions were not found in the analyzed dialogues. The results suggest that the film emphasizes natural, expressive communication, with a strong focus on information sharing, emotional expression, and maintaining social interaction. These functions support the narrative’s romantic and dramatic elements, as well as highlight character development and relationships. Overall, this study offers valuable insights into how language is used effectively in film dialogue to reflect social relationships, convey emotional depth, and fulfill communicative intent. It contributes to the broader understanding of language use in media and provides a model for analyzing other films from a sociolinguistic perspective.